REVISING SYNTACTIC INTERFERENCE ON CONVERSATION SCRIPTS BY CONTRASTIVE ANALYSIS TEACHING METHOD - Ida Ayu Putri Gita Ardiantari (Universitas Lambung Mangkurat, 2022)
Abstract: This study is a research to the third semester of DIV Midwifery students of Kartini Polytechnique Denpasar on Bahasa Inggris I class. The purpose of this research are (1) to identify the syntactic interference of Indonesian Language into English found in conversation scripts written by the third semester of DIV Midwifery students and (2) to investigate the quality of English conversation scripts after the application of contrastive analysis method. The data of this study were taken from English conversation scripts written by the third semester of DIV Midwifery students of Kartini Polytechnique. The interview and observation method also used in collecting the data of this research to find out the students understanding in English syntactic structure. The data were grouped, tabulated and analyzed through sociolinguistic theory of interference that supported by Surface Strategy Taxonomy as well, and the Contrastive Analysis Hypothesis. Based on the analysis, the syntactic interferences found are in level of phrase, clause and sentence; and the error caused by omission, addition, and mis-formation. The interview and observation method showed the increase of the student understanding in English syntactic structure after the application of contrastive analysis method that effect the better quality of English conversation scripts.